Diseño de un prototipo funcional mecánico para extraer el cristal del aloe vera, para la empresa Colombia S.A, en el departamento del Huila. - Torres Rada, Felix Mauricio (Universidad Antonio Nariño, 2022)
This project aims to design a functional electromechanical prototype to extract the crystal from aloe vera, for the company KOLOMBIA S.A, in the department of Huila. With this prototype it is planned to first prepare the material to be able to extract the Aloe Vera crystal. The virtual model is developed from the academic Solidworks program to be manufactured in the company of Kolombia S.A. For which a theoretical and technical investigation was carried out, where the proposed objectives are met in the course of this investigation, resulting in; in the first place, the study of several researchers with preliminary works that allowed specifying the manner and steps necessary for the extraction of the aloe crystal.